Digital Marketing Strategy, Brand Awareness, Application of Big Data Technology, Impact on Business Success - Lutfiani, Ami; Kartawan, Kartawan; Abdullah, Yusuf (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2024)
This research aims to examine the direct and indirect influence of digital marketing strategies, brand awareness and the application of big data technology, their impact on business success. The study was conducted on consumers online shop daster convection in Tasikmalaya. Sampling is carried out using techniquespropotioned startisfied random sampling, with a total sample size of 240 respondents, who are regular customers who transact every month at the Mimima Fashion, Beauty Hijab Tisa and Irma Laila store convections. The research instrument used was a questionnaire with a Likert scale. The analysis technique used is path analysis using the SPSS version 27 application. The results of this research show that: 1) Digital marketing strategy and business success are in very good condition, while brand awareness and application of big data technology are in good condition. 2) Digital marketing strategies, brand awareness and the application of big data technology partially have a positive and significant effect on business success. 3) Digital marketing strategy, brand awareness and the application of big data technology simultaneously have a significant influence on business success for consumers of the daster convection online shop in Tasikmalaya. Keywords :Business Success, Brand Awareness, Digital Marketing Strategy, Big Data Technology.